How do individuals respond when probabilities are imprecise? - Thawornrat, Nattapong (2012)
Abstract Probability, the simple number and represent chance of occurrence of certain event in the future, is a tool that aids decision making for a very long time. For many decades that studies of people choice focus on probability and even name it as benchmark for rational decision. However, in late 1970, many researchers started to question its whether it is possible to calculate exact number that represents chance of occurrence in reality. The most influent paper which bring this curiosity of imprecise probability into public is the papers of Daniel Ellsberg and his colour ball lottery. In this paper we will investigate on how people respond to imprecise probabilities base on Ellsberg paradox in more realistic control in order to exclude every bias such as bias that may derive from forced choice that Dhar and Simonson (2003) describe which may affect the outcome of the experiment. Then the relationship between characteristics and risk attitude will be illustrated. Keywords: Ellsberg’s paradox, Imprecise probability, Forced choice